2017
DOI: 10.1117/1.oe.56.5.051406
|View full text |Cite
|
Sign up to set email alerts
|

Review of conformal displays: more than a highway in the sky

Abstract: Abstract. A head-worn display combined with accurate head-tracking allows one to show synthetically generated symbols in a way that they appear as a part of the real world. Depending on the specific research context, different terms have been used for the ability to show display elements as parts of the outside world. These include contact analog, scene linked, augmented reality, and outside conformal. While the famous highway in the sky was one of the first applications in avionics, over the years more and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…One of the most important HMI design paradigms in this context is the concept of "(visual) conformal symbology". The idea behind that is to show "synthetically generated symbols in spatial relation to real world objects" [13]. Also, the concept of "scene-linking" is closely related to this.…”
Section: Head-worn Display Symbologymentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important HMI design paradigms in this context is the concept of "(visual) conformal symbology". The idea behind that is to show "synthetically generated symbols in spatial relation to real world objects" [13]. Also, the concept of "scene-linking" is closely related to this.…”
Section: Head-worn Display Symbologymentioning
confidence: 99%
“…[14]). Further, scene-linked symbols are commonly used to highlight waypoints, obstacles, or other points of interest [13].…”
Section: Head-worn Display Symbologymentioning
confidence: 99%
“…Research at the Technical University of Munich showed that the use of AR HMD to display flight paths and obstacles can decrease pilot workload during landing operations in DVE (Viertler and Hajek, 2017). This improves SA and collision awareness using 3-D conformal visualization of obstacles through symbolic representation of geospatial frame of reference (Peinecke et al, 2017). Obstacle visualization, 3 D conformal display of pathways-on-the-ground, and 3-D safe landing zone visualization are also valuable assets in DVE flight conditions, especially for low altitude flight and landings in unprepared areas (Viertler and Hajek, 2017).…”
Section: Navigationmentioning
confidence: 99%
“…Four additional top-downloaded papers were review papers on laser feedback interferometry, 4 head-mounted displays for air transportation, 5 terahertz photoconductive antenna technology, 6 and conformal displays. 7 The final three in the top-ten download list included special section papers on white light interferometric microscopy 8 and anisoplanatic imaging through turbulence, 9 along with a regular paper on laser-induced damage of camera sensors. 10 All of these papers are available with open access, which is a likely factor in the high number of downloads.…”
Section: Year In Reviewmentioning
confidence: 99%